2017
DOI: 10.1016/j.omtn.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of the Bifunctional HIV Entry Inhibitor sCD4-FI T45

Abstract: HIV entry into target cells is a highly sequential and time-sensitive process. In recent years, potent HIV Env-targeting antibodies, such as VRC01, have been identified. However, antibodies bind only to a single epitope, and mutations that confer resistance to antibody-mediated inhibition of HIV entry have been detected. In contrast, HIV cannot escape from binding to soluble CD4 (sCD4) without a fitness disadvantage. sCD4 has the unique ability to induce conformational changes within the HIV envelope glycoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…We and other groups have shown that sCD4 can be covalently linked to synergistic inhibitors, such as sCD4-induced epitope-targeting antibody fragments (e.g., sCD4-scFv 17b ), CCR5-mimicking peptides (e.g., eCD4-immunoglobulin [Ig]), or fusion inhibitors (e.g., 2DLT or sCD4-FI T45 ). 37 , 68 , 69 , 70 , 71 The resulting bifunctional proteins drastically improved the antiviral effect of sCD4 without enabling infection of CD4-negative cells. Furthermore, bifunctional inhibitors should also minimize the emergence of escape mutants.…”
Section: Discussionmentioning
confidence: 99%
“…We and other groups have shown that sCD4 can be covalently linked to synergistic inhibitors, such as sCD4-induced epitope-targeting antibody fragments (e.g., sCD4-scFv 17b ), CCR5-mimicking peptides (e.g., eCD4-immunoglobulin [Ig]), or fusion inhibitors (e.g., 2DLT or sCD4-FI T45 ). 37 , 68 , 69 , 70 , 71 The resulting bifunctional proteins drastically improved the antiviral effect of sCD4 without enabling infection of CD4-negative cells. Furthermore, bifunctional inhibitors should also minimize the emergence of escape mutants.…”
Section: Discussionmentioning
confidence: 99%
“… 100 , 101 To overcome the limitations of single inhibitors, several inhibitors have also been combined, e.g., sCD4 was fused to a co-receptor-mimicking peptide or fusion inhibitors. 102 , 103 , 104 , 105 Aside from inhibiting HIV entry, several AVPs have the advantage that they can also reduce the cytopathic effects of HIV replication and mediate the elimination of infected cells. For example, antibodies and sCD4 can neutralize free gp120 in the serum of HIV-positive individuals or gp120 on the surface of infected cells.…”
Section: Main Textmentioning
confidence: 99%
“…The resulting fusion protein sCD4-FI T45 was a potent inhibitor of HIV entry and neutralized isolates that were resistant to sCD4, FI T20 , or VRC01. 164 , 165 Lu et al. 166 have also fused sCD4 to the second-generation FI T1144 by using a seven-repeat GGGGS linker (2DLT).…”
Section: Main Textmentioning
confidence: 99%
“… 177 In contrast, the bAVPs eCD4-Ig and sCD4-FI T45 are significantly more effective against HIV strains that are relatively resistant to CD4-binding site bnAbs; the eCD4-Ig and sCD4-FI T45 IC 50 s for the same clade C isolate are below 0.1 μg/mL. 158 , 165 …”
Section: Main Textmentioning
confidence: 99%